The Role Of Organizational Culture, Employee Engagement And Work Environment In Employee Performance - Erwina; I Dewa Gede Adi Pratama Tenaya; Ofriyanto Paidjo; Eni Palayuk; Corie Ewnike Tuar (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
Employee performance constitutes a critical determinant of organizational success, particularly within the public service sector. This study examines the influence of organizational culture, employee engagement, and work environment on employee performance at Perumdam Waemami, East Luwu Regency, Indonesia. The research adopts a quantitative methodological approach. A sample of 62 employees was determined using the Slovin formula, selected through incidental sampling technique. Data collection was conducted through three methods: structured interviews, direct observation, and questionnaire surveys. The data were analyzed employing descriptive analysis and Structural Equation Modeling using Partial Least Squares (SEM-PLS). The findings reveal that organizational culture exerts no significant influence on employee performance, while employee engagement and work environment demonstrate significant positive effects on employee performance. These results indicate that while organizational culture showed limited impact, high levels of employee engagement and a supportive work environment play pivotal roles in enhancing employee performance at Perumdam Waemami, East Luwu Regency.